ANALISIS PEMASARAN KARET PETANI EKS UPP TCSDP DI DESA LUBUK SAKAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Dotik Komala Dewi; Evy Maharani (Indonesian Journal of Agricultural Economics, 2016)
This research aim to analyze the marketing channel, marketing margin, farmer’s share, marketing efficiency of rubber for EX UPP TCSDP farmers at Lubuk Sakai Village Kampar Kiri Tengah District in Kampar Regency. The research method used survey method. The sampling method in this research used purposive sampling with criteria of rubber crop age ranging from 21-23 years for 30 rubber farmers. Intake of sample to rubber compiler and factory used snowball sampling method by following its marketing channel. The research result in Lubuk Sakai Village Kampar Kiri Tengah District in Kampar Regency that two marketing channel. The research result show that one marketing channel is good and efficient for marketing channel I, that was rubber farmers to small compiler next to big compiler to factory. Total cost of marketing channel I equal Rp. 2.319,00/kg total value of margin equal to Rp. 2.250,00/kg , farmer’s share equal to 73,84% and marketing efficiency equal to 26,97%. Total cost of marketing channel II equal Rp. 2.370,13/kg total value of margin equal to Rp. 2.028,00/kg , farmer’s share equal to 76,42% and marketing efficiency equal to 27,56%.